Ionized outflows in local luminous AGN: what are the real densities and outflow rates?. Issue 3 (2nd September 2020) - Davies, R; Baron, D; Shimizu, T; Netzer, H; Burtscher, L; de Zeeuw, P T; Genzel, R; Hicks, E K S; Koss, M; Lin, M-Y; Lutz, D; Maciejewski, W; et al.
ABSTRACT: We report on the determination of electron densities, and their impact on the outflow masses and rates, measured in the central few hundred parsecs of 11 local luminous active galaxies. We show that the peak of the integrated line emission in the active galactic nuclei (AGN) is significantly offset from the systemic velocity as traced by the stellar absorption features, indicating that the profiles are dominated by outflow. In contrast, matched inactive galaxies are characterized by a systemic peak and weaker outflow wing. We present three independent estimates of the electron density in these AGN, discussing the merits of the different methods. The electron density derived from the [S ii ] doublet is significantly lower than that found with a method developed in the last decade using auroral and transauroral lines, as well as a recently introduced method based on the ionization parameter. The reason is that, for gas photoionized by an AGN, much of the [S ii ] emission arises in an extended partially ionized zone where the implicit assumption that the electron density traces the hydrogen density is invalid. We propose ways to deal with this situation and we derive the associated outflow rates for ionized gas, which are in the range 0.001–0.5 M⊙  yr −1 for our AGN sample. We compare these outflow rates to the relation between $\dot{M}_{\rm out}$ and L AGN in the literature, and argue that it may need to be modified and rescaled towards lower mass outflow rates.